APLIKASI SISTEM PAKAR KOPI MENDETEKSI HAMA KOPI DI DESA TELAGAH KECAMATAN SEI BINGAI KABUPATEN LANGKAT - Butar, Pedro Chandra M Butar; Siregar, Ameilia Zuliyanti (Jurnal Agroteknologi, 2024)
The use of coffee expert applications can help farmers detect pest attacks based on symptoms of attacks on coffee plants. This study aims to determine the application of the coffee expert system to coffee farmers, determine the diversity of insect species and pest status on coffee plants in Telagah Village, Sei Bingai District, Langkat Regency, North Sumatra. Insect identification was carried out by the Plant Pest Laboratory, Faculty of Agriculture, University of Sumatra Utara which was carried out from July to August 2023. This study used purposive sampling method with yellow sticky trap. The results showed insects caught as many as 10 orders, 21 families, 25 genera as many as 4743 individuals. The results of the analysis of Coffee Experts detected Hypothenemus hampei pest attack = 6.80%. Diversity Index (H') = 1.91, evenness index (E) = 0.59 and species richness index (R) = 8,46. The use of coffee expert applications can help farmers detect pests appropriately.